2022
DOI: 10.3390/sym14050888
|View full text |Cite
|
Sign up to set email alerts
|

Lateralization Direction, Strength, and Consistency in Juvenile and Adolescent Idiopathic Scoliosis: A Case Control Pilot Study

Abstract: The aim of this study was to assess the hypothesis that functional laterality features are associated with scoliosis incidence. The study included 59 patients with radiologically confirmed idiopathic scoliosis (mean age 13 years, 41 girls and 18 boys) and 55 controls (mean age 10.5 years, 38 girls and 17 boys). Side dominance was determined by the Lateral Preference Inventory. Direction, strength, and consistency of lateral dominance was obtained. Continuous data were compared by Student’s t-test or U Mann-Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…However, it must be noted that the spine is influenced by multifaceted mechanical factors. Lateral trunk shifts can precipitate spinal deviation, suggesting that handedness and dominance patterns could contribute to such shifts (25). Persistent postures that favor the dominant side may promote trunk imbalance, potentially leading to asymmetries that require clinical attention to prevent the progression into conditions like scoliosis (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be noted that the spine is influenced by multifaceted mechanical factors. Lateral trunk shifts can precipitate spinal deviation, suggesting that handedness and dominance patterns could contribute to such shifts (25). Persistent postures that favor the dominant side may promote trunk imbalance, potentially leading to asymmetries that require clinical attention to prevent the progression into conditions like scoliosis (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies conducted to examine the laterality of trunk asymmetry and side dominance have focused on diagnosed adolescents with AIS and on the region that is more prevalent in the spine rather than the side of the spine [11][12][13][14][15]20,21]. However, Arienti et al (2019) [14] found that right-side dominance was associated with a prevalence of 0.43%, 1.01% and 0.87% for right thoracic, right thoracolumbar and left lumbar curves, respectively.…”
Section: Lateralitymentioning
confidence: 99%
“…Laterality in children and adolescents has also been also examined to indicate a significant association of scoliosis-related attributes (curve pattern and convexity) with the direction of hand preference, the strength of the asymmetry direction or side preference consistency [11][12][13][14][15]. Yang and Li (2011) developed a theory with a three-dimensional spring Adolescents 2024, 4 63 model and a hypothesis for the mechanism of left-right handedness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation